1994
DOI: 10.1093/jpepsy/19.6.751
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Problematic Mealtime Interactions of Children with Cystic Fibrosis and Their Parents Via Behavioral Parent Training

Abstract: Implemented behavioral parent training targeting maladaptive mealtime behavior with two children with cystic fibrosis (CF) and their parents. Treatment was implemented in multiple baseline fashion across the two families. Primary dependent measure was coding of parent and child behaviors from videotaped dinners. Data were also collected on the children's daily calorie intake and weight. During treatment and at the posttreatment follow-ups, parents' attention to disruptive behavior decreased, attention to appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 0 publications
2
54
0
Order By: Relevance
“…Our prior work indicates that such behaviors may be amenable to change via behavioral interventions (17,18). Specifically, helping families establish rules and consequences for meal duration and staying at the table may be needed.…”
Section: Parenting Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Our prior work indicates that such behaviors may be amenable to change via behavioral interventions (17,18). Specifically, helping families establish rules and consequences for meal duration and staying at the table may be needed.…”
Section: Parenting Stressmentioning
confidence: 99%
“…In the only study to focus solely on preschoolers with type 1 diabetes, Wysocki et al (6) found that parents reported mealtime problems as some of the more challenging aspects of diabetes care (e.g., "My child leaves the table during meals" and "My child dawdles a long time before coming to the table"). As our prior work in cystic fibrosis has shown (13)(14)(15)(16)(17)(18), research examining the impact of nutrition management on families and young children with type 1 diabetes could serve to inform the development of behavioral interventions designed to make such disease-specific tasks more manageable for this understudied population.…”
mentioning
confidence: 99%
“…This study suggests this may be a promising area to address, especially because of the potential association with child weight status. Behavioral interventions have shown promise in decreasing child problematic eating and increasing parental control as well as improving weight and caloric intake in children [19][20][21]. In one such intervention called Be In Charge!…”
Section: Discussionmentioning
confidence: 99%
“…The most common example of extinction, in a feeding disorder treatment context, is to ignore undesired child behaviors such as refusals or tantrums [32,50]. Often, extinction techniques are difficult for parents to implement, and learning these techniques may require in vivo training for caregivers which might include modeling, behavior reversal, and practice to refine caregivers' skills and to provide emotional support during intervention.…”
Section: Behavioral Treatmentmentioning
confidence: 99%